Inkjet printing of two-dimensional van der Waals materials: a new route towards emerging electronic device applications - Cho, Kyungjune; Lee, Takhee; Chung, Seungjun (Royal Society of Chemistry, 2022)
Two-dimensional (2D) van der Waals (vdW) materials are considered one of the most promising candidates to realize emerging electrical applications. Although until recently, much effort has been dedicated to demonstrating high-performance single 2D vdW devices, associated with rapid progress in 2D vdW materials, demands for their large-scale practical applications have noticeably increased from a manufacturing perspective. Drop-on-demand inkjet printing can be the most feasible solution by exploiting the advantages of layered 2D contacts and advanced 2D vdW ink formulations. This review presents recent achievements in inkjet-printed 2D vdW material-based device applications. A brief introduction to 2D vdW materials and inkjet printing principles, followed by various ink formulation methods, is first presented. Then, the state-of-the-art inkjet-printed 2D vdW device applications and their remaining technical issues are highlighted. Finally, prospects and challenges to be overcome to demonstrate fully inkjet-printed, high-performance 2D vdW devices are also discussed.